Teacher And Student Directive Speech Actions In Online Teaching Learning Interactions At SMP Ignatius Global School Palembang - Meidini, Ayu; Suhendi, Didi; Izzah, Izzah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The primary purpose research to discuss the form and function of the directive speech acts of teachers and students in online teaching and learning interactions at SMP IGS Palembang.The method used in this research is descriptive qualitative. Sources of data in this study are speech acts that contain directive speech acts of students and teachers in online teaching at SMP IGS Palembang. Based on the results of the analysis, it was found that there were forms and functions of teacher and student directive speech acts and teacher transactions were found in the discourse of classroom interaction in online teaching and learning interactions. The forms of teacher directive speech acts that appear in online teaching and learning interactions are requertives, question, requirements, prohibitives, permissives, and advisorie. The forms of student directive speech acts that appear in online teaching and learning interactions are requertives, question, and advisories. This research is limited to discussing only directive speech acts of teachers and students in teaching and learning interactions. This research can contribute to students, teachers and other researchers regarding directive speech acts that occur in online teaching and learning interactions.